BORNAGE OF CHILDREN'S LEARNING DURING PANDEMIC AND TEACHER'S EFFORT IN OVERCOMING IT - Rahmi Arsita Br Ginting; Riska Khadijah (Proceeding International Seminar of Islamic Studies, 2022)
The emergence of the COVID-19 pandemic brought enormous changes to human life, one of which was in the field of education. Every student must have experienced boredom at the time of learning, especially at this time. This research is qualitative using triangulation technique. This study aims to find out what are the factors that cause child learning boredom during the pandemic and how the teacher's efforts to overcome it. The saturation of children's learning that occurs during the pandemic is due to different learning techniques and makes children unable to play with friends or teachers directly. The efforts of teachers in overcoming child boredom during a pandemic are by making varied learning methods, using interesting learning media, making quizzes at the end of learning, establishing communication between parents.Keywords:Learning Saturation, Pandemic, Teacher's Efforts